Conflict and Family Law Issues in Shia Groups - Hidayah, Okti Nur (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2025)
This article discusses the dynamics of Sunni-Shia relations in Indonesia by highlighting anti-Shia campaigns, the experiences of discrimination against the Shia community, and sensitive issues such as interfaith marriage and mut'ah marriage. Using historical, social, and theological approaches, this study shows that the marginalization of Shia Muslims is not only influenced by doctrinal differences, but also by transnational ideologies, state policies, and pressure from conservative groups. Cases such as the 2012 Sampang tragedy and conflicts involving the Rausyan Fikr Foundation in Yogyakarta are concrete examples of escalating intolerance. The findings of the article show that resistance to discrimination has emerged from moderate Muslim figures, but these efforts have not been able to neutralize the dominance of anti-Shia discourse in the public sphere. In addition, studies on interfaith marriage and the debate on mut'ah marriage illustrate how differences in Sunni-Shia jurisprudence affect family and social life. This article concludes that the Shia issue in Indonesia is a multidimensional problem that requires inclusive dialogue, legal protection for minorities, and a moderate approach to maintain intra-Islamic harmony in Indonesia.